2020
DOI: 10.3389/fonc.2020.599218
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Endoscopic Diagnosis of Helicobacter pylori Based on the Kyoto Classification of Gastritis: A Multicenter Study

Abstract: BackgroundThere is lack of clinical evidence supporting the value of the Kyoto classification of gastritis for the diagnosis of Helicobacter pylori (H. pylori) infection in Chinese patients, and there aren’t enough specific features for the endoscopic diagnosis of past infections, which is of special significance for the prevention of early gastric cancer (GC).MethodsThis was a prospective and multicenter study with 650 Chinese patients. The H. pylori status and gastric mucosal features, including 17 character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 30 publications
0
29
0
Order By: Relevance
“…Figure 1 demonstrates patterns of H. pylori-positive gastric mucosae. On the other hand, the presence of RAC in the corpus10 (Figure 2), fundic gland polyps, and red streaks (Figure 3) were associated with H. pylorinegative gastric mucosa with a sensitivity/specificity of 92.4%/94.5%, 20.4%/96.9%, and 19.5%/95.4%, respectively (Zhao et al, 2020).…”
Section: Conventional Wlimentioning
confidence: 97%
“…Figure 1 demonstrates patterns of H. pylori-positive gastric mucosae. On the other hand, the presence of RAC in the corpus10 (Figure 2), fundic gland polyps, and red streaks (Figure 3) were associated with H. pylorinegative gastric mucosa with a sensitivity/specificity of 92.4%/94.5%, 20.4%/96.9%, and 19.5%/95.4%, respectively (Zhao et al, 2020).…”
Section: Conventional Wlimentioning
confidence: 97%
“…Nodularity, diffuse redness, mucosal swelling, enlarged fold and sticky mucus were significantly associated with current infection. Map-like redness was responsible for past infection, and the overall diagnostic accuracy rate of Kyoto classification of gastritis was more than 80% [41][42][43][44]. Furthermore, with regard of uninfected status, one study showed RAC had excellent negative predictive value (NPV) of about 90% and sensitivity value of up to 85% [45].…”
Section: Conventional White Light Imaging (Wli)mentioning
confidence: 99%
“…The Kyoto Classification of Gastritis, categorizing H. pylori infection into three phases (non-gastritis, active gastritis, and inactive gastritis[ 54 ]), was proposed to better assess the status of H. pylori infection and GC risk by endoscopy[ 55 ] (Figure 1 ). In a healthy stomach, an easily detectable feature, non-gastritis, was the regular arrangement of collecting venules (RAC), featured as small red spots on the mucosal surface[ 56 , 57 ]. However, after being infected with H. pylori , the stomach was characterized as irregular arrangement or absence of the so-called collecting venules[ 58 ].…”
Section: Changes In Endoscopic Findings After H Pylori Eradicationmentioning
confidence: 99%